Teacher Perceptions of Independent Curriculum Implementation in Madrasah Ibtidaiyah: A Phenomenological Study at MI Podorejo Tulungagung - Faiqotul Himmah (Yayasan Centre for Studying and Milieu Development of Indonesia (CESMiD), 2025)
This study examines teachers’ perceptions of the implementation of the Independent Curriculum at MI Podorejo Tulungagung, following the national shift from the 2013 Curriculum to the new competency- and character-based model. Many teachers continue to experience confusion regarding curriculum components, instructional strategies, and assessment practices, making perception an important determinant of implementation quality. This research aims to analyze teachers’ understanding of the curriculum concept, their instructional roles, and the challenges and solutions encountered during the implementation process. Using a qualitative phenomenological design, data were collected through in-depth interviews with the principal, curriculum coordinator, and Grades 3, 4, and 5 teachers, supported by relevant school documentation. The findings reveal that the Independent Curriculum has been implemented in accordance with its core principles, emphasizing flexible, student-centered learning and character development through the P5RA project. Teachers primarily act as facilitators and motivators who guide students toward independent and exploratory learning. However, several obstacles remain, including limited teacher understanding of new curriculum terminology, administrative workload, adaptation of teaching modules, parental involvement, and difficulties selecting appropriate learning methods. Madrasah-initiated solutions include capacity-building workshops, parental socialization sessions, and the provision of supporting learning resources. These results highlight the need for sustained institutional support and enhanced teacher capacity to ensure the effective implementation of the Independent Curriculum.